2014
DOI: 10.4238/2014.january.17.3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the GSTT1 and GSTM1 genes are associated with increased risk of preeclampsia in the Mexican mestizo population

Abstract: ABSTRACT. Preeclampsia is a pregnancy-specific disorder in humans and a major cause of maternal and neonatal morbidity and mortality. Increasing evidence suggests that oxidative stress plays an important role in the pathogenesis of preeclampsia. The aim of this study was to investigate the relationship between null alleles of the glutathione S-transferases (GST) M1 and T1 genes and the risk of preeclampsia. This case-control study involved 112 preeclamptic and 233 normoevolutive pregnant women. The null polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…In the present study, we observed similar null GSTM1 genotype frequencies in our control group at those that had been previously reported in Mexico (Pérez-Morales et al, 2011;Martínez-Ramírez et al, 2013;Sandoval-Carrillo et al, 2014). The genotypic GSTM1 null frequencies were 38 and 45% in the control group and in patients with BC, respectively, suggesting an association of this allele as a risk factor in BC.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the present study, we observed similar null GSTM1 genotype frequencies in our control group at those that had been previously reported in Mexico (Pérez-Morales et al, 2011;Martínez-Ramírez et al, 2013;Sandoval-Carrillo et al, 2014). The genotypic GSTM1 null frequencies were 38 and 45% in the control group and in patients with BC, respectively, suggesting an association of this allele as a risk factor in BC.…”
Section: Discussionsupporting
confidence: 74%
“…Several reports in the general Mexican population have described a high frequency of the null GSTM1 allele of approximately of 37-44%, depending on the tested region (Pérez-Morales et al 2011;Martinez-Ramirez et al, 2013;Sandoval-Carrillo et al, 2014). However, there are no descriptions to date of an association of the null GSTM1 polymorphism with BC in Mexican women.…”
Section: Introductionmentioning
confidence: 97%
“…Since the pivotal role of GST enzymes in the mechanisms related to antioxidant defense and cellular detoxification, a number of studies investigated the role of GST genetic variations in oxidative stress-related diseases [11,12]. Regarding GH, some research groups focused on the role of deletion polymorphisms of the GSTT1 and GSTM1 genes affecting the risk of preeclampsia, obtaining disagreeing results [13,14]. However, the biochemical investigation of GST levels confirmed the significant dyshomeostasis of GST systems in preeclampsia:…”
Section: Introductionmentioning
confidence: 87%
“…They also found no association between GSTM1 gene polymorphism and pre‐eclampsia. Study conducted by Sandoval‐Carrillo et al . found a significant relation with GSTT1 null genotype and the risk of pre‐eclampsia in Mexican mestizo population.…”
Section: Discussionmentioning
confidence: 95%
“…found significant relationship between GSTT1 null genotype with pre‐eclampsia in the Chinese population. Another study on Mexican population showed higher risk of developing pre‐eclampsia in patients having GSTT1 null genotype and even higher risk for GSTT1 and GSTM1 combined null genotype . Another study on Iranian population revealed that there was no association of GSTT1 and GSTM1 gene polymorphism with pre‐eclampsia .…”
Section: Introductionmentioning
confidence: 99%